Teacher-student interaction in mathematics learning - Irma Ayuwanti; Marsigit Marsigit; Dwi Siswoyo (International Journal of Evaluation and Research in Education (IJERE), 2021)
Teacher-students interaction is one of the most important interactions in learning. Teacher-students interaction affects student understanding.However, in practice, there are still many lessons that have not applied teacher-students interaction properly.This study aimed to reveal teacher-student interaction in the mathematics learning process that affects students’ mathematical understanding.This study used a qualitative method with a phenomenological approach.Theresearch subjects were eighth-grade junior high school students. Research data were obtained through observation, interviews, and documentation.Observations were conducted in the eighth grade and interviews were conducted with six students from the class. The students were interviewed to express their opinions concerning learning process interactions. The results of this study showed that teacher-student interaction has affected students’ mathematical understanding consists of: 1) The teacher transfers the material-the students attend to the material; 2) Question-answer amid teacher-students; 3) The teacher makes interesting learning strategies-students are actively involved in learning; 4) Teachers give awards-students receive awards.